The book by Alexei Gordeyev "Church on the Maidan" - The Protestant Chronology of the Revolution of Virtue - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2015)
And here is another testimony of an event that entered into the history not only of Ukraine, but also of its neighbors, of Europe, of all of Sviati. Some believe that modern history is divided into "before" and "after" the Maidan, regardless of how we treat it. The book, published by the publishing house "Knigonosha" (K., 205), gives the position of those who were on the Maidan, who saw everything with their own eyes, who has the experience of "Maydanivtsi", who can testify. And readers can trust or not trust this information. Much depends on the reader himself, on the way of his thinking, on life experience. For some, the Maidan is a Revolution of Dignity, and for others, a coup d'état.